A cross-sectional study on iodine status among pregnant and non-pregnant women of Tripura: a North-Eastern state of India - Majumder, Nilratan; Sutradhar, Balaram; Riang, Saradindu; Datta, Shib Sekhar (International Journal of Research in Medical Sciences, 2019)
Background: Due to excess metabolic demand of iodine in pregnancy, pregnant women and lactating mother and their neonates are most vulnerable of iodine deficiency disorder. Urinary iodine excretion is a good marker of recent dietary iodine intake. Thus, present study was conducted to assess the iodine status and median urinary iodine excretion (UIE μg/lit) among pregnant and non-pregnant women of Tripura. Methods: Tribal and Bengali pregnant and non-pregnant women from Bokafa and Jolaibari Block of South Tripura district were included in the study. Urinary iodine excretion was done using simple micro plate method. Salt iodine was estimated using iodometric titration. All the tests were performed at CNRT Lab, ICMR, India. Results: Total number of subjects included in this study was 1071. Total number of urine samples collected from pregnant and non-pregnant women was 538 and 533 respectively. Median value of UIE in pregnant and non-pregnant women of Tripura was 155.0µg/L and 130.0µg/L. In pregnant women percentage prevalence of severe (<20µg/L), moderate (20-49µg/L) and mild iodine deficiency (50-149µg/L) was found in 4.1%, 15.1% and 29.6% subjects. In case of non-pregnant women severe (<20µg/L), moderate (20-49µg/L) and mild iodine deficiency (50-99µg/L) was found in 0.6%, 9.6%, 27.8% subjects respectively. The overall prevalence of iodine deficiency was found in 48.8% pregnant women, compared to 38.0% non-pregnant subjects. Conclusions: Efforts towards universal salt iodization need to be stepped-up in Sub-Himalayan region (NE part of India) and pregnant and lactating mothers may be targeted with alternate iodine supplements (Colloidal Iodine).